- 3


xmnk xk+1

³ xmnk.

:

xmnk+2

= min (xk+2, min (k+1, k)) = Min (k+2,

k+1, k).

, xk , ..., xi

mni = Min (k, ..., i).

. i = k + 1, k + 2 ­. , (i + 1)- . , :

xi+1

i+1 < xmni = min(xi+1, mni)

mni+1

=

mni i+1 ³ mni = min(xi+1, xmni)

= min (xi+1, Min (k , ..., i)) = Min (k, ..., i, xi+1).

. , ­ ­ :

xmnN

= Min (xk, ...,

N)

.

2.

{ xmn = Min (k, ..., N) }

xi¢mn= xk

k' = Min (k, ..., N).

. 1 xmn = Min (xk, ..., N). k' =

xmn,

k' = xmn = Min (k, ..., N).

.

. 1', ..., N', ­ 1' £ 2' £ ... £ N'.

. :

k = 1 N - 1

xmn

:= k

............... { xmn = Min (k, ..., i) }

¢k

= xmnN

m¢

= k

{ k' = Min (k, ..., N) }

{ 1' £ 2' £ ... £ k' }